General Information About Power Steering and Their Advantages and Disadvantages - Pulatovich, Magdiyev Shovkat; Iskandarovich, Rakhmatov Murodjon; Zayniddinovich, Sharopov Zavqiddin (European Journal of Life Safety and Stability (2660-9630), 2023)
Power steering, Power steering, Power steering, Advantages and disadvantages of power steering, Advantages and disadvantages of power steering.